TSNI 2021 - Textbook: Focus on Students’ National Identity 2021
DOI: 10.3897/ap.e4.e0699
|View full text |Cite
|
Sign up to set email alerts
|

Folklore Tale for Young Children Precuring a Polyculture Textbook

Abstract: The development of benevolent relationships between people of different races and ethnicities living in the same areas, such as the city of Moscow is highly relevant modern issue can be beneficially addressed in early childhood. This article discusses challenges of multicultural education in Moscow preschools and kindergartens. Folk tales characterized as an early precursor of a textbook for children who do not attend a school and cannot read. The article depicts the ability of folk tales to introduce young ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Polkovinikova et al (2021) employed a survey study in Moscow preschool centers ( N = 8) with Russian parents ( N = 388) and teachers ( N = 241) to enumerate the presentation of folk tales used to transmit ethnic identity information to children. The survey included questions about children's ethnic identities and the kinds of stories parents and teachers used to socialize children ethnically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polkovinikova et al (2021) employed a survey study in Moscow preschool centers ( N = 8) with Russian parents ( N = 388) and teachers ( N = 241) to enumerate the presentation of folk tales used to transmit ethnic identity information to children. The survey included questions about children's ethnic identities and the kinds of stories parents and teachers used to socialize children ethnically.…”
Section: Resultsmentioning
confidence: 99%
“…Although the sample was diverse in racial and ethnic composition, adults reported that Russian folk tales were almost exclusively used to socialize children to ethnic identities; folk tales from other races and ethnicities were not reported. The researchers concluded that folk tales are a useful symbolic tool to socialize young children ethnically, and multicultural societies could use folk tales from multiple ethnic groups to foster tolerance and knowledge of neighboring ethnic identities in preschoolers (Polkovinikova et al, 2021).…”
Section: Resultsmentioning
confidence: 99%